2018
DOI: 10.1111/cbdd.13348
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose as a novel template for anticancer drug development targeting galectins

Abstract: Galectins are carbohydrate binding proteins (lectins), which characteristically bind β-galactosides. Galectins play a role in tumour progression through involvement in proliferation, metastasis, angiogenesis, immune evasion and drug resistance. There is need for inhibitors (antagonists) that are specific for distinct galectins and that can interfere with galectin-carbohydrate interactions during cancer progression. Here, we propose that lactulose, a non-digestible galactose-fructose disaccharide, presents a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The binding mode of the ring of this galactose exhibits characteristic interactions exhibited by galectins with galactose when integrated as a component of endogenous ligands, for example, lactose (Figure 2a). The interactions between galectin-3 CRD and galactose ring are consistent and also observed in structures of galectin-3 CRD with bound galactose-based derivatives (Atmanene et al, 2017;Collins et al, 2007;Kishor, Ross, & Blanchard, 2018).…”
Section: Affinity Studiessupporting
confidence: 80%
“…The binding mode of the ring of this galactose exhibits characteristic interactions exhibited by galectins with galactose when integrated as a component of endogenous ligands, for example, lactose (Figure 2a). The interactions between galectin-3 CRD and galactose ring are consistent and also observed in structures of galectin-3 CRD with bound galactose-based derivatives (Atmanene et al, 2017;Collins et al, 2007;Kishor, Ross, & Blanchard, 2018).…”
Section: Affinity Studiessupporting
confidence: 80%
“…It was reported that treatment with thiogalactoside (TDG) 14 or lactulose 22 reduced adipocyte differentiation and obesity in murine fed a HFD. TDG and lactulose is a non-metabolized disaccharide that can bind to galectins, and inhibit the function of intracellular and extracellular galectins 23 . In this study, the inhibition of extracellular galectins by lactose did not affect adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, the CRDs of galectins are arranged in a tightly folded conserved beta-sandwich structure formed by a six-stranded sheet (S1–S6) and a five stranded sheet (F1–F5). Figure 1 shows the structure of gal-1 (Kishor et al ., 2018), gal-3 (Saraboji et al ., 2012) and gal-4 (Rustiguel et al ., 2016). The carbohydrate-binding amino acids are in strands S4–S6 (Rini and Lobsanov, 1999; Loris, 2002) and they have been highlighted (Fig.…”
Section: Structure Of Host Galectinsmentioning
confidence: 99%
“…There is considerable diversity in the amino acid sequences. The amino acids implicated in binding to carbohydrate in galectin-1 (Kishor et al ., 2018) have been identified as His44, Asn46, Arg48, His52, Asn61, Trp68, Glu71 and Arg73. Of these eight sites, only Trp68 is conserved among all the prototypic galectins.…”
Section: Structure Of Host Galectinsmentioning
confidence: 99%